2023
DOI: 10.1002/smtd.202201140
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Lithium Metal with Garnet Electrolyte by Interfacial Lithiophobicity/Lithiophilicity Transition Mechanism over 380 °C

Abstract: Garnet electrolytes, possessing high ionic conductivity (10−4–10−3 S cm−1 at room temperature) and excellent chemical/electrochemical compatibility with lithium metal, are expected to be used in solid‐state lithium metal batteries. However, the poor solid–solid interfacial contact between lithium and garnet leads to high interfacial resistance, reducing the battery power capability and cyclability. Garnet electrolytes are commonly believed to be intrinsically lithiophilic, and lithiophobic Li2CO3 on the garnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Figure d demonstrates stable cycling over 60 cycles with the Coulombic efficiency being maintained at almost 100%. Additionally, Figure e compares the current density, areal capacity, and areal loading of the NA-LLZTO prepared for the full battery with those of other advanced solid-state batteries. ,,,, The designed Li/NA-LLZTO/LFP full battery shows prominent advantages in terms of practical application (detailed information is provided in Table S1). As shown in Figure S18, the battery exhibits clear charge–discharge profiles and maintains lower voltage polarizations.…”
Section: Resultsmentioning
confidence: 99%
“…Figure d demonstrates stable cycling over 60 cycles with the Coulombic efficiency being maintained at almost 100%. Additionally, Figure e compares the current density, areal capacity, and areal loading of the NA-LLZTO prepared for the full battery with those of other advanced solid-state batteries. ,,,, The designed Li/NA-LLZTO/LFP full battery shows prominent advantages in terms of practical application (detailed information is provided in Table S1). As shown in Figure S18, the battery exhibits clear charge–discharge profiles and maintains lower voltage polarizations.…”
Section: Resultsmentioning
confidence: 99%
“…Garnet-type solid electrolytes have gained significant attention in recent years due to their stability. They exhibit good chemical compatibility with lithium metal and possess high ionic conductivity, which leads to enhanced safety and energy density in lithium ion batteries. , To address the issue of dendrite growth, lithium garnet (Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 , LLZTO) particles and lithium salt-free poly­(ethylene oxide) (PEO) were used to create a composite film by Zhang et al Remarkably, this solid electrolyte film demonstrated no dendrite growth even after 700 h of cycling. The nanoscale lithium ion conducting particles effectively improved electrical conductivity, while the insulating PEO in the PEO:LLZTO film electrolyte inhibited dendrite growth due to current limitations.…”
Section: All-solid-state Lithium Batterymentioning
confidence: 99%
“…On the other hand, limited publications studied the effect of surface microstructures on the wetting behaviors of molten metals on substrates at high temperatures, while most of them concerned about the composition of the melts and the substrate surfaces or the periphery conditions. ,, , Lai et al found that a microporous copper substrate enhanced the wetting of molten Sn, while Zhou et al structured the steel mold surfaces to weaken the adhesion of the molten and resolidified Al alloys with the mold by preventing their full wetting. Liu et al discussed the effect of laser-textured stainless steel surface structures on the wetting and spreading behaviors of the Al–Si alloy in the presence of flux, and Lin et al observed that rough silica surfaces improved the spreading of the Sn–Ag–Ti alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The melting of metals (and alloys) at high temperatures is a common phenomenon in many industrial processes, e.g., metallurgy, refining, casting, welding, and brazing. Recently, molten metals have also been proposed to be potential novel materials in various fields, such as newly developed batteries and nuclear fusion. The wetting of molten metals on various substrate surfaces has a great impact on related processes and applications, significantly affecting the processing feasibility and product performance. However, only few literature studies focused on the wettability of molten metals at high temperatures (e.g., 1000 °C) compared with the wettability studies on more common liquids under more gentle conditions, such as water and low-melting-point liquid metals at room temperature. Various simulations have been performed to predict the probable wetting behaviors of molten metals on various substrates, but practical observations remain scarce due to the availability of materials and the strict environmental requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation